PREVALENSI DAN FAKTOR RISIKO TUNGAU DEBU RUMAH DI PAMULANG (TANGERANG) DAN PASAR REBO (JAKARTA) - Subahar, Rizal; Widiastuti, Widiastuti; Aulung, Agus (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2016)
House dust mites (HDM), anaeroallergen which may be found in all of part of the urban house including mattress. The objectives of this study were to find out the prevalence and risk factors of house dust mites in urban communities i.e.,Pamulang (Southern Tangerang) and Pasar Rebo (Nothern Jakarta). The study design was a cross-sectional study. The samples of house dusts were collected from house of respondents, living-room floors, bed-room floors, kitchen-room floors, terrace-room floors, ventilation, kapuk mattress, sofa, spring bed, foam mattress, and carpet. Mites were examined by a direct method. The species of HDM found were Dermatophagoides pteronyssinus, D.farinae, and Glyciphagus destructor. The prevalence rate ofHDM was 66,9% (621/927). Statistically, no significant difference(p>0,05) was found between the prevalence of HDM in Pamulang(59,8% ,307/513) and Pasar Rebo (75,8%, 314/414). In Pamulang, 94.2% (49/52)of the respondent’s houses were HDM positive (+) and 63.6% (28/44) in Pasar Rebo. Mattresses and bed-room floors were risk factors for HDM(OR=1.99 95% CI 1.06-3.72 and OR=1.8 95% CI 1.10-2.90). This study showed that the houses in two urban communities hadrich HDM.